Exploring undergraduate students' experience of using ChatGPT in EFL Academic writing classroom - Nisa, Dwi Devi Khoirotun; Basya, Dihliza; Nugraheni, Dyah Ayu (Mell Baou Publisher, 2025)
This study explores the experiences of Indonesian undergraduate students using ChatGPT in their English as a Foreign Language (EFL) academic writing classes. It begins by addressing the inherent challenges EFL learners face in academic writing, such as difficulties with grammar, coherence, and vocabulary. The research employs a qualitative methodology, specifically narrative inquiry, to gather insights from students through semi-structured interviews. The findings indicate that students find ChatGPT to be a valuable resource that assists them in various aspects of the writing process, including generating ideas, structuring sentences, and correcting grammar. This support leads to noticeable improvements in the quality of their writing, such as enhanced clarity and vocabulary diversity. However, the study also identifies several challenges, including inconsistencies in the responses generated by ChatGPT, issues with the validity of the information provided, and ethical concerns regarding plagiarism and originality. Overall, the thesis emphasizes the importance of critical engagement with AI tools like ChatGPT, suggesting that while they can significantly aid the writing process, students must be cautious and informed about their use. The research highlights the need for educators to provide clear guidelines on the ethical implications of using AI in academic writing, ensuring that students can maximize the benefits while minimizing potential drawbacks.